2015
DOI: 10.1097/mpa.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Colonization of Pancreatic Duct Stents

Abstract: Microbial analysis of pancreatic duct stents revealed a very high colonization rate. Furthermore, the spectrum and number of microorganisms altered with the indwelling time of the stent. However, clinical relevance of our findings remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…A recent study by Schneider et al. found gram‐negative organisms such as Enterobacteriaceae were significantly more prevalent on stents with a longer indwelling time . Although not statistically significant in this study, patients with bacterial contamination experienced a longer median duration of chronic pancreatitis (6.3 vs 3.9 years, P =.30), a factor that may have contributed to the number of Enterobacteriaceae isolated in culture.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…A recent study by Schneider et al. found gram‐negative organisms such as Enterobacteriaceae were significantly more prevalent on stents with a longer indwelling time . Although not statistically significant in this study, patients with bacterial contamination experienced a longer median duration of chronic pancreatitis (6.3 vs 3.9 years, P =.30), a factor that may have contributed to the number of Enterobacteriaceae isolated in culture.…”
Section: Discussioncontrasting
confidence: 68%
“…Studies have demonstrated the sterility and antimicrobial capacity of pancreatic fluid, and researchers have postulated that any bacterial colonization of pancreatic tissue is likely due to iatrogenic manipulation of the pancreatic duct . Ascending bacterial colonization can occur through retrograde migration from the intestinal lumen (more likely after pancreatic surgery) or through the formation of a biofilm on the surface of pancreatic duct stents . More specifically, a recent study by Hill et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klebsiella species (most commonly K. pneumonia and K. oxytoca ) are ubiquitous gram-negative organisms that cause nosocomial infections in humans 25 and commonly harbor genes for antibiotic resistance 26 . Several prior studies of the microbiology of the jejunum 18 , biliary tree 8,2731 , and pancreas 7 also identified an abundance of Klebsiella in patients with gallstone disease, cholangitis, and cancer. This pattern of results suggests that conditions within the pancreas and biliary tree are favorable for colonization by Klebsiella species, particularly in the setting of disease.…”
Section: Discussionmentioning
confidence: 92%
“…It has been clearly shown that enteric or biliary microbes can colonize the inflamed pancreas in experimental models 5 . Similarly, it has been shown that the pancreatic duct or stents within the duct in the setting of chronic pancreatitis contain a rich biofilm containing bacteria 6,7 . The bile duct has also been considered to be generally sterile 6 but a number of studies have demonstrated the presence of bacteria in the biliary system in the setting of bile duct obstruction 6,8,9 .…”
Section: Introductionmentioning
confidence: 98%